2014
DOI: 10.1186/s12985-014-0199-7
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous alteration of residues 279 and 284 of the VP2 major capsid protein of a very virulent Infectious Bursal Disease Virus (vvIBDV) strain did not lead to attenuation in chickens

Abstract: BackgroundCell culture adaptation of very virulent infectious bursal disease virus (vvIBDV) was shown to be mainly associated with the VP2 capsid protein residues 253, 279, and 284. The single mutation A284T proved critical for cell culture tropism, but did not confer efficient virus replication, which at least required one additional mutation, Q253H or D279N. While the double mutation Q253H/A284T was unambiguously shown to confer both efficient replication in cell culture and attenuation in chickens, conflict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 42 publications
(53 reference statements)
0
7
0
Order By: Relevance
“…Virulence classification groups these viruses into classical virulent (cv), subclinical variant, and very virulent (vv) IBDV strains (Ben Abdeljelil et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Virulence classification groups these viruses into classical virulent (cv), subclinical variant, and very virulent (vv) IBDV strains (Ben Abdeljelil et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Virulence declined rapidly when vvIBDV with amino acid mutations at positions 253 and 284 in the VP2 hypervariable region was passaged serially in chicken embryo fibroblast cells [18], while the very virulent pathogenicity was restored after a reverse mutation assay. Recent virulence and immunology studies have shown that the amino acid residue at position 253 is critical to the alteration of virulence of IBDV, while the residues at positions 279 and 284 are not directly related to viral virulence but are involved in cell adaptability and replication efficiency [19,20]. All these studies suggest that a few amino acid mutations at key positions in the VP2 hypervariable region can have significant impacts on the virulence of IBDV.…”
mentioning
confidence: 99%
“…Position 279 has been shown to be involved in the ability to replicate in chicken embryonic fibroblasts (Lim et al 1999 ). However, this does not necessarily imply a lack of pathogenicity in chickens (Abdeljelil et al 2014 ). In addition, 279 residue have been described as one of the positions affected by passages in DT40 cells, which are a tumor cell line derived from the bursa of Fabricius of a chicken infected with avian leukosis virus (Terasaki et al 2008 ; Delgui et al 2009 ).…”
Section: Resultsmentioning
confidence: 99%